If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + 1 = 3X + -11 Reorder the terms: 1 + 2X = 3X + -11 Reorder the terms: 1 + 2X = -11 + 3X Solving 1 + 2X = -11 + 3X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3X' to each side of the equation. 1 + 2X + -3X = -11 + 3X + -3X Combine like terms: 2X + -3X = -1X 1 + -1X = -11 + 3X + -3X Combine like terms: 3X + -3X = 0 1 + -1X = -11 + 0 1 + -1X = -11 Add '-1' to each side of the equation. 1 + -1 + -1X = -11 + -1 Combine like terms: 1 + -1 = 0 0 + -1X = -11 + -1 -1X = -11 + -1 Combine like terms: -11 + -1 = -12 -1X = -12 Divide each side by '-1'. X = 12 Simplifying X = 12
| 7+2X+1=3X-11 | | y+80=-45 | | n-24=-16 | | -54+m=82 | | 30x^2-44x+16=0 | | y+8=21 | | a-9=13 | | 4x-3(x-2)=16 | | 250+14h=22h | | 3=5x+12 | | t+(2t+4)=-5 | | 8x/3-5x/4=-13 | | 5/25=y/85 | | -(5b+5)-5=1-(5b-1) | | -36=4w | | 11=3-7x | | X^3-2X+0.5=0 | | X^3-2X-0.5=0 | | 22=2c | | -2(2(2)-4)=-4(-2+2) | | 4x^2+9x-2=0 | | .90x+.52(2-x)=.10(-118) | | 3x-16cm=200cm | | 7x+2[3(1-x)]=14 | | 3(t+2)-(3t-3)=2(3t-4)-13 | | 3(t+2)-(3t-3)=2 | | 64=8n | | (x+3)-2c-(1-3x)=2 | | 6w^3-28w+16=0 | | .5y+2=.8y-.3 | | x=4x+96 | | 2w-6m=50m |